Five essays on doing research on adult learning in times of pandemic and war: thinking aloud - Evans, Rob (Adult Education Discourses, 2023)
It is easy “not” to save the world, an Italian writer remarked at the end of 2022 (Piccolo, 2022). Saving the world is difficult. But serious researchers who seek to do just that are not going to be moved by current world crises to stop doing their research. The seriousness of the research they do is an obvious reason for pushing on. Another is that they are committed, concerned people who take their work very seriously, passionately even. They are, of course very different by professional formation, cultural-linguistic background and temperament. Age, as well, and gender separates, differentiates them. They are united in their common praxis, however, which – to borrow the words of Bernie Grummell and Fergal Finnegan – can be described as “the craft of research as a practical, ethical and theoretical endeavour” (Grummell & Finnegan, 2020: 1) whose common driving force in many cases is a democratic and collaborative ethic which seeks to identify and foster progressive transformative possibilities for individuals, communities and society through research, teaching and learning (Grummell & Finnegan, 2020: 2). The crises that are universally seen as piling up in a seemingly endless series of threatening catastrophes imperiously demand a response from us therefore as researchers.